Pengaruh Influencer Attributes, Influencer Trustworthiness, dan Brand Image Terhadap Purchase Intention - Islamiyah, Tasya Firdhausi; Hapsari, Raditha Dwi Vata (Jurnal Manajemen Pemasaran dan Perilaku Konsumen, 2023)
The objective of this research is to identify the effects of influencer attributes, influencer trustworthiness, and brand image on the purchase intention of the Rachel Goddard’s review video viewers on YouTube. This research is considered as an explanatory study as it elucidates the causal relationship between research variables through hypothesis testing. Using non-probability sampling method and purposive sampling technique, 156 people with the minimum age of seventeen years and have viewed the review video published by Rachel Goddard through her YouTube channel at least two time in the last three months were selected as the sample. The data was analyzed using multiple linear regression, and the hypotheses were tested using the t-test; all of which were performed in SPSS 25. This study finds that influencer attributes positively and significantly influence the purchase intention, that influencer trustworthiness positively and significantly affects the purchase intention, and that brand image positively and significantly impacts the purchase intention. Based on those finding, it can be inferred that Rachel Goddard can increase her interaction with more varied social media followers and improve the creation of positive information about the products that she may review.   Abstrak Penelitian ini memiliki tujuan untuk mengetahui pengaruh dari influencer attributes, influencer trustworthiness, dan brand image terhadap niat pembelian atau purchase intention pada penonton video ulasan di kanal youtube Rachel Goddard. Penelitian ini merupakan jenis penelitian eksplanatori yang menjelaskan hubungan kausal antar variabel penelitian melalui pengujian hipotesis. Teknik pengambilan sampel menggunakan non-probability sampling dengan metode purposive sampling. Ukuran sampel yang digunakan adalah sebanyak 156 responden dengan ketentuan menonton video ulasan dari kanal youtube Rachel Goddard minimal dua kali dalam kurun waktu 3 bulan terakhir dan berusia lebih dari 17 tahun. Analisis data menggunakan Analisis Regresi Linier Berganda dan uji hipotesis menggunakan Uji t yang diolah pada software SPSS 25. Berdasarkan dari hasil pengujian terhadap ketiga hipotesis dapat disimpulkan bahwa, influencer attributes memiliki pengaruh yang positif signifikan terhadap purchase intention, influencer trustworthiness memiliki pengaruh yang positif dan signifikan terhadap purchase intention, dan brand image memiliki pengaruh yang positif dan signifikan terhadap purchase intention. Implikasi penelitian antara lain Rachel Goddard dapat melakukan peningkatan interaksi dengan pengikut melalui sosial media yang lebih bervariasi, penciptaan informasi positif mengenai produk dapat ditingkatkan.